The Impact of Non-Performing Loans and Economic Shock on The Stability of Islamic Banking Performance as Moderating Variable in The COVID-19 Pandemic Era - Zainuri Zainuri; Suryaning Bawono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine the effect of non-performing loans and economic shock as an intervening variable on loanable supply and loanable demand in Islamic banks which have an impact on the stability of the performance of Islamic banks in the Pandemic era. The research period is monthly with the research period from June 2019 – June 2021 using behavioral data analysis. We use secondary data from the Indonesian financial services authority. We investigated the data using linear and non-linear analysis to investigate the influence of loanable supply and loanable demand on the performance of Islamic banks in normal times or in a stable economy and the occurrence of economic shocks. From the results of our investigation, we found that non-performing loans have a significant impact on loan supply and loan demand in influencing the stability of the performance of Islamic banks in the era of the COVID-19 pandemic. Performance shocks in Islamic banks in the pandemic era are not only due to economic shocks but also due to non-performing loans from Islamic bank customers who are unable or have difficulty completing their obligations to Islamic banks.